Shear wave velocity measurements using acoustic radiation force impulse in young children with normal kidneys versus hydronephrotic kidneys - Sohn, Beomseok (Korean Society of Ultrasound in Medicine, 2014)
PURPOSE: To measure shear wave velocities (SWVs) by acoustic radiation force impulse (ARFI) ultrasound elastography in normal kidneys and in hydronephrotic kidneys in young children and to compare SWVs between the hydronephrosis grades. METHODS: This study was approved by an institutional review board, and informed consent was obtained from the parents of all the children included. Children under the age of 24 months were prospectively enrolled. Hydronephrosis grade was evaluated on ultrasonography, and three valid ARFI measurements were attempted using a high-frequency transducer for both kidneys. Hydronephrosis was graded from 0 to 4, and high-grade hydronephrosis was defined as grades 3 and 4. RESULTS: Fifty-one children underwent ARFI measurements, and three valid measurements for both kidneys were obtained in 96% (49/51) of the patients. Nineteen children (38.8%) had no hydronephrosis. Twenty-three children (46.9%) had unilateral hydronephrosis, and seven children (14.3%) had bilateral hydronephrosis. Seven children had ureteropelvic junction obstruction (UPJO). Median SWVs in kidneys with high-grade hydronephrosis (2.02 m/sec) were higher than those in normal kidneys (1.75 m/sec; P=0.027). However, the presence of UPJO did not influence the median SWVs in hydronephrotic kidneys (P=0.362). CONCLUSION: Obtaining ARFI measurements of the kidney is feasible in young children with median SWVs of 1.75 m/sec in normal kidneys. Median SWVs increased in high-grade hydronephrotic kidneys but were not different between hydronephrotic kidneys with and without UPJO.